Does financial literacy drive SME success in resource-rich regions? - Ariswati, Lusiana Desy; Kesuma, Muhammad Ramadhani; Aini, Rohana Nur; Irianto, Ellen D. Oktanti; Widaryo, Chandika Mahendra; Henrika, Margareth (Privietlab, 2025)
This study investigates the relationships among financial literacy, product innovation, risk management, and financial performance in small and medium-sized enterprises (SMEs) located in East Kalimantan, a region in Indonesia characterized by its resource abundance. While prior studies underscore the importance of financial literacy and innovation for SME success, there is limited research focusing on non-urban, commodity-reliant settings. Using a quantitative methodology, this study employs Partial Least Squares Structural Equation Modeling to analyze data gathered from 200 SME owners in non-extractive industries through a structured survey. This study explores whether financial literacy and product innovation directly affect financial performance and whether risk management mediates these dynamics. The findings reveal that financial literacy has a significant positive effect on financial performance, whereas product innovation strengthens risk management but does not directly influence financial outcomes. Additionally, risk management does not mediate these relationships, indicating potential contextual constraints in resource-limited environments. These insights advance the understanding of SME operations in non-urban, resource-dependent regions and highlight the need for customized financial education and innovation. This study provides actionable recommendations for policymakers to enhance SME resilience through targeted strategies, addressing a key gap in the literature on economies tied to natural resources.